Application Of 2-D Resistivity And Self-Potential Methods In Delineating Water Flow - Mahmud, Nazirah (2022)
Water flow is essential for engineers when constructing any form of structure. A vital factor to consider is water flows through the soil can impact the engineering and environmental aspects. In recent years, the self-potential (SP) method was rarely found in dealing with the water flow issue. In this research, 2-D resistivity and SP methods have been chosen to detect the potential area of water flow. Geophysical methods are non-standalone methods as the data might be affected by the surrounding environment. The integrations of geophysical and geotechnical methods are performed to increase the understanding of subsurface features and water flow. 2-D resistivity can identify the position of conductive materials in the subsurface. SP measures the natural potential of the Earth, such as electrokinetic potential, which arises when water flows through the subsurface. The auger samples and borehole data were used to support the geophysical interpretation. As a result, the potential area of water was identified at low resistivity area (< 200 Ωm) and low SP value which indicate as recharge zone.